(untitled) (Research, Society and Development, 2020)
Objective: Analyze the profile of suicides in the county of Marabá-PA, between 2015 and 2019. Methods: Quantitative, cross-sectional, retrospective study, which used information from the medical records and death certificates of the Instituto Médico Legal de Marabá-PA, which took place from January 1, 2015 to December 31, 2019. Descriptive and analytical statistics were performed in BioEstat® software 5.4. For decision-making, the significance level α = 0.05 or 5% was adopted. Results: There was a higher incidence of suicides in 2017, single men were the most identified victims. The highest frequency of suicides occurred in the age group of 30 to 39 years, in the color / brown race, in people with complete high school education, in the urban area and in their own residence. The main mechanism was mechanical asphyxiation. Most deaths involved a single injury. Conclusion: Mortality in young male adults stood out, highlighting the relevance of this investigation, as it allows the subsidy of campaigns to prevent the mental health of target audiences in the creation of coping strategies for this population.